2019
DOI: 10.1002/macp.201900412
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Thermosensitive Poly(N‐Vinyl Caprolactam)‐Grafted‐Aminated Alginate Hydrogels

Abstract: Thermosensitive hydrogels are characterized by the drastic and reversible change of their physical properties with temperature. Herein is presented the development of a thermosensitive poly(N‐vinylcaprolactam)‐grafted‐aminated alginate (PNVCL‐g‐Alg‐NH2) having a temperature‐dependent phase transition close to physiological temperature. The hybrid copolymer is formed through the combinational use of chemical and physical methods, that is, carbodiimide chemistry, and ionotrophic gelation by calcium cations. PNVC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Durkut et al (2020) characterized in vitro performance of a PNVCL-g-Alg-NH 2 copolymer with cytotoxicity and hemocompatibility assays, culturing human dermal fibroblast. Cell viability increased from ~85% to approximately 95% when aminated alginate proportion was diluted from 1/1 to 1/4 [ 65 ]. Further research is necessary to carry out in vivo investigation.…”
Section: Methodsmentioning
confidence: 99%
“…Durkut et al (2020) characterized in vitro performance of a PNVCL-g-Alg-NH 2 copolymer with cytotoxicity and hemocompatibility assays, culturing human dermal fibroblast. Cell viability increased from ~85% to approximately 95% when aminated alginate proportion was diluted from 1/1 to 1/4 [ 65 ]. Further research is necessary to carry out in vivo investigation.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, copolymerization with PNVCL reduced the water absorption of aminated alginate and enhanced its thermal stability. Biocompatibility studies, including in vitro cytotoxicity and blood compatibility analyses, confirmed the nontoxicity of PNVCL-g-Alg-NH 2 scaffolds and their lack of haemolytic effects [236].…”
Section: Phycocolloids As Potential Drug Delivery Systemmentioning
confidence: 68%
“…The hydrogel exhibited a continuous release of DOX-encapsulated In addition, the temperature-responsive properties of alginate gels offer a wide range of potential applications as smart drug carriers. Durkut et al [236] developed a thermosensitive polymer known as poly(N-vinylcaprolactam)-grafted aminated alginate (PNVCL-g-Alg-NH 2 ), which underwent a phase transition and expansion upon water absorption at approximately 35 • C, making it suitable for physiological temperature conditions. Moreover, copolymerization with PNVCL reduced the water absorption of aminated alginate and enhanced its thermal stability.…”
Section: Phycocolloids As Potential Drug Delivery Systemmentioning
confidence: 99%
“…However, making thermosensitive PSA is not limited to PNIPAM grafting. Poly­( N -vinyl­caprolactam)-grafted-aminated alginate (PNVCL- g -Alg-NH 2 ) also shows thermoresponsive features . Moreover, making IPNs based on a PSA and a thermosensitive polymer is another robust method to make PSA-based thermosensitive polymers .…”
Section: Tailor-made Psas For Biomedical Applicationsmentioning
confidence: 99%